Peer feedback among international PhD students - Kobayashi, Sofie (Improving University Science Teaching and Learning, 2023)
This presentation of my project mirrors my own development in thinking about feedback and formative assessment. In the first part, Problem statement and intervention design, I discuss peer feedback without defining precisely what I mean by this concept. That is done deliberately as I was not myself very precise in my thinking about feedback at the time of designing the project. In later sections I develop my thinking about feedback, to the broader concept of formative assessment.